80‐1: Invited Paper: Recent Development of Soluble Hole Injection Material for OLED Display. Issue 1 (29th May 2019) - Monzen, Kazuhiro; Maeda, Daisuke; Higashi, Masayuki; Endo, Toshiyuki
Abstract : We are developing the soluble hole injection materials and the inks, named ELsource ® that can be used as hole injection layer in OLED display. OLED display is one of optical device. Therefore, we developed the hole injection materials with optical properties necessary for that optical device.